2005
DOI: 10.2320/matertrans.46.2309
|View full text |Cite
|
Sign up to set email alerts
|

Isothermal Fatigue Properties of Sn–Ag–Cu Alloy Evaluated by Micro Size Specimen

Abstract: Micro-bulk fatigue testing developed to investigate the fatigue lives and damage mechanisms of Sn-3.0Ag-0.5Cu and Sn-37Pb solder alloys. The fatigue life of micro-bulk solder obeyed Manson-Coffin's empirical law, and the fatigue ductility exponents were about 0.5 for both Sn-Ag-Cu and Sn-Pb alloys. The fatigue life of Sn-3.0Ag-0.5Cu alloy was 10 times longer than that of Sn-37Pb alloy under symmetrical cycling at 298 K, although fatigue resistance of Sn-3.0Ag-0.5Cu alloy was not very superior under asymmetrica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 16 publications
(26 reference statements)
1
40
1
Order By: Relevance
“…More details of the procedure can be found in the previous report. 6) Tensile test specimens were aged at 120 C for 168 h and 504 h in an oil bath before the tensile test to investigate the effect of aging on the mechanical properties. Microstructural observations were performed for the cross-sections of the gauge regions by electron probe X-ray microanalysis (EPMA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…More details of the procedure can be found in the previous report. 6) Tensile test specimens were aged at 120 C for 168 h and 504 h in an oil bath before the tensile test to investigate the effect of aging on the mechanical properties. Microstructural observations were performed for the cross-sections of the gauge regions by electron probe X-ray microanalysis (EPMA).…”
Section: Methodsmentioning
confidence: 99%
“…[2][3][4] However, it was pointed out that the microstructure of the conventional bulk specimen does not correspond with that of the real solder joint, since the real solder joint is miniaturized and it is difficult to duplicate the solidification conditions of the real joint in the bulk specimen. 5,6) Kariya and co-workers developed a new testing method for solder alloys and joints using micro size specimens having analogous size and microstructures to those of real solder joints. [5][6][7][8][9] They reported that the creep properties of the micro size specimen of a Sn-3 mass%Ag-0.5 mass%Cu solder differ from those of the bulk specimen under low stress.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16][17][18][19][20] Development of electronic devices accelerates downsizing of the solder joints, and currently grid arrays of a solder ball of about 100 mm in diameter are used in electronic devices. Therefore it is emphasized 11) that mechanical properties of the solder material should be testified with small size specimens comparable to the solder joints because their mechanical properties are largely influenced by microstructures, which are dependent on the cooling rate in the soldering process. The authors [21][22][23] studied the fatigue properties of solder joints with tin solder and Sn-Ag-Cu alloy solder, and found when the solder joints with a thin solder layer of 60 mm in thickness was subjected to a repeated loading, not only a peripheral crack propagated at the edge of the bonded region but also fine penny-shaped cracks appeared in the bonded region.…”
Section: Introductionmentioning
confidence: 99%
“…When electronic devices are installed in machineries, such as automobiles, these devices suffer repeated loading and thermal cycling to cause degradation of the solder joints, and finally to result in failure. To prevent catastrophic failures, lots of studies have been carried out on the fatigue and thermo-mechanical fatigue behaviors of the lead-free solder [1][2][3][4][5][6][7][8][9][10][11][12][13] and solder joints. [14][15][16][17][18][19][20] Development of electronic devices accelerates downsizing of the solder joints, and currently grid arrays of a solder ball of about 100 mm in diameter are used in electronic devices.…”
Section: Introductionmentioning
confidence: 99%